Kekuatan Hukum Tindakan Represif Kepolisian dalam Unjuk Rasa yang Mengakibatkan Kericuhan - Ryan Sukma Wibawa (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This study aims to analyze the legal authority in regulating police repressive actions during demonstrations, with a special focus on the rejection of the UU Cipta Kerja in Indonesia. Legal authority is a fundamental principle in the legal system that determines the extent to which regulations or policies bind individuals or entities. This study employs qualitative research methods through literature review to delve into the legal authority of police repressive actions in demonstrations, considering factors such as the law-making process, the hierarchy of legal regulations, and developments in law and its interpretations. The research findings indicate a gap between legal regulations and field practices, particularly related to challenges in implementation and enforcement of the law. The study also explores how repressive actions, often involving the use of physical force and arrests, impact human rights, including freedom of expression and assembly. The implications of these findings highlight the importance of accountability and effective oversight in law enforcement to ensure that police actions are proportionate and respect individual rights. This research contributes to a deeper understanding of the legal framework governing police repressive actions and paves the way for improvements in police practices and the protection of individual rights in similar situations.